Simulation of light propagation in the optical interconnection base on noble metal nanoparticle - Guo, Yina (2015)
Although vast amounts of data zip across the Internet each day in the form of light waves conveyed by optical fibers, today's computing systems still rely on electrical signals traveling through a dense network of metal lines linking together gigantic numbers of nanoscale devices on silicon chips, which have much lower bandwidth. Reduction in the pitch and cross-section of metal lines gives rise to local heating and an increase in the RC delay of interconnected structures via the metal lines. Optical interconnects will provide the solution because they do not exhibit such problems and have a much higher information carrying capacity due to the much higher operating frequencies (optical frequencies are about 100,000 times greater than the frequency of today's electronic microprocessors). In this project, the student is going to conduct a simple simulation of light propagation in optical interconnects based on gold nanoparticle arrays using a commercial software. The research will include the simulation of the energy transfer in a nanoscale waveguide and the study of the influence of the size/spacing of the gold nanoparticles on the energy transfer. The FYP student will work closely with the PhD student who is currently working on the related projects.